Hubungan Minat Belajar Warga Belajar dengan Hasil Belajarnya dalam Mata Pelajaran Bahasa Inggris Program Paket B PKBM Generasi Muda Lubuk Basung - Ayu Salsabilla Mustika; Wirdatul Aini (Dinasti Research, 2023)
The background of this research is the low learning outcomes of the students in the English Subject of Package B Program PKBM Young Generation of Lubuk Basung. This study aims to: 1) describe the learning interests of the learning community; 2) describe the learning outcomes of learning residents; and 3) look at the relationship between the learning interest of the learning community and their learning outcomes in the English Subject of the Package B Program PKBM for the Young Generation of Lubuk Basung. This research uses a quantitative approach and the type of research is descriptive correlational. The population of this study were all 30 students learning English in the PKBM Young Generation package B program. The sampling technique that the researchers used was cluster random sampling of 20 people. The data collection technique used in this study was a questionnaire, with a data collection tool in the form of a questionnaire guide. The data analysis technique in this study uses the proportion formula and rank correlation order. The results showed that: (1) the learning interest of the focused learners was still low, (2) the learning outcomes of the focused learners were still low, (3) there was a significant relationship between the learning interests of the learning residents and their learning outcomes in the Package B Program English Subject. PKBM Lubuk Basung Young Generation. It is suggested to tutors to be able to vary the learning methods used to attract students' interest in learning so that students get maximum learning outcomes.